DISPOSAL OF HOUSEHOLD WASTE AT THE SITES OF THEIR CREATION WITH OBTAINING FUEL GAS - ENSURING SAFETY IN WASTE HANDLING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the concept of mankind, solid household waste began to enter in the 50-60s of the last century. The text of this article describes the norms of collection, removal, morphological composition of solid household waste, and methods of their processing.